Analisis Faktor-Faktor Yang Mempengaruhi Purchase Intention Konsumen Kendaraan Listrik Di Kota Medan - Dwi Rahmawaty; Sarah Imelda; Tapi Rondang Ni Bulan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the factors influencing consumers’ purchase intention toward electric vehicles in Medan City. A quantitative approach was employed with a total sample of 123 respondents selected through purposive sampling. The independent variables consist of Attitude (X1), Subjective Norms (X2), Perceived Behavioral Control (X3), Price Value (X4), Perceived Risk (X5), Environmental Self-Image (X6), and Infrastructure Barrier (X7), while the dependent variable is Purchase Intention (Y). Data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that Attitude (X1), Perceived Behavioral Control (X3), Environmental Self-Image (X6), and Infrastructure Barrier (X7) have a positive and significant effect on consumers’ purchase intention toward electric vehicles in Medan City. Meanwhile, Subjective Norms (X2), Price Value (X4), and Perceived Risk (X5) show no significant effect on purchase intention. Therefore, it can be concluded that consumers’ positive attitudes, perceived behavioral control, environmental self-image, and adequate infrastructure support are key factors that enhance consumers’ intention to purchase electric vehicles in Medan City.